A study of Bianchi type I spacetime according to their Ricci collineations - Akhtar, Sumaira Saleem; Ahmad, Israr; Shakeel, Mehnaz; Zahir, Hina; İnç, Mustafa (Springer, 2024)
Rici collineations (RCs) have been used in this research to study the locally rotationally symmetric (LRS) Bianchi type I spacetimes. To accomplish our objectives, the RC equations are typically integrated for both situations of the Ricci tensor, degenerate and non-degenerate. Throughout this work, a number of situations occur that provide various finite and infinite dimensional Lie algebras of RCs.
Keywords: Einstein field equation; Bianchi type I spacetime; Ricci collineations